Antibacterial property of lead telluride quantum dot layer fabricated on glass substrate - Samuel Onuh Abuh; Svetlana Lyssenko; Ayan Barbora; Iryna Hovor; Faina Nakonechny; Refael Minnes (PLoS ONE, 2025)
Lead Telluride (PbTe) is a narrow band gap semiconductor alloy with excellent thermoelectric properties for several energy harvesting applications. However, the antibacterial properties of PbTe quantum dots (QDs) have not been investigated. PbTe QDs were synthesized using simple spin-coating method and deposited on Titanium dioxide layered ITO glass substrates. The resulting layers of PbTe QDs on the substrates were characterized using high-resolution scanning electron microscope, energy-dispersive X-ray spectroscopy, Fourier transform infra-red spectroscopy and contact angle measurement. The characterization results showed thin layers of PbTe quantum dots with mean sizes 6.1 ± 0.5 nm, 9.8 ± 0.7 nm, and 13.2 ± 1.1 nm and reduced surface wettability. PbTe QDs were tested for their antibacterial activity against Gram-positive bacteria Staphylococcus aureus and Gram-negative Escherichia coli, Salmonella Paratyphi B and Pseudomonas aeruginosa. The antibacterial effect of the QDs was estimated using the zones of inhibition to bacterial growth. The results show excellent antibacterial activity of PbTe QDs towards Gram-negative bacteria. FTIR micro-spectroscopy suggests disruption of cell boundaries as possible mechanism of antibacterial action of PbTe QDs. Given the demonstrated antibacterial effectiveness, the PbTe QDs can be considered for nanocoating bacterial-prone surfaces like solar panels to minimize bacterial colonization and improve system performance.